Evaluation of the Genotoxicity of the Aerial Parts of Iraqi Euphorbia cyathophora on Bone Marrow and Spleen Cells in Mice - Jaafar, Noor Sabah; Ali F Hassan; Maha N Hamad (Iraqi Journal of Pharmaceutical Sciences, 2023)
The aim of the study was extraction of arial part of Euphorbia cyathophora constituents with methanol and evaluate its effect on mitotic index and total chromosomal aberration bone marrow cell and spleen cell in mice 200 gm of E. cyathophora fine powder was defatted then extracted by cold maceration 80% ethanol for seven days. The extract was filtered and dried in a rotary evaporator then the dried extract was suspended with water and consecutively extracted using chloroform, ethyl acetate for each. The aqueous layer was then mixed with 100ml methanol. These fractions are dried under reduced pressure to obtain the dry extract. Twenty-four Albino mice were used for the experiment. The animals were divided into four groups: Group 1: Mice were treated with distilled water. The dose was given daily for seven successive days. Group 2: Mice were treated with a single dose (20mg/kg) of methotrexate (positive control). Group 3: Mice were treated with (100mg/kg) of menthol fraction for seven successive days. Group 4: Mice were treated with (200mg/kg) of methanol fraction for seven successive days. Mice were sacrificed by (spinal dislocation). Samples of bone marrow cells and spleen cells were taken and genotoxic analyses. Methanol fraction of Euphorbia cyathophora at a dose of 100mg/kg demonstrated a significant decrease in mitotic index and a significant increase in total chromosomal aberrations as compared to distilled water in both bone marrow cells and spleen cells (p<0.05). 100 mg/kg and 200 mg/kg of methanol fraction of Euphorbia cyathophora that showed to be significantly higher in mitotic index and significantly lower in total chromosomal aberration as compared to methotrexate (p<0.05). In conclusion the current study revealed that the methanol fraction of aerial parts of Euphorbia cyathophora is genotoxic but its genotoxicity is less than that of methotrexate.